Effect of conductivity transportation from carbon nanotubes (CNT) to polymer matrix surrounding CNT on the electrical conductivity of nanocomposites. Issue 4 (14th December 2019) - Zare, Yasser; Rhee, Kyong Y.; Park, Soo‐J.
Abstract: In this article, the interphase thickness in polymer carbon nanotubes (CNTs) nanocomposites (PCNT) is correlated to CNT radius and the extent of conductivity transportation from CNT to polymer matrix surrounding the CNT ( K ). In addition, CNT properties and " K " are applied to suggest the simple equations for percolation threshold and the fraction of networked CNT. A simple model is developed to predict the conductivity of PCNT assuming CNT size, " K " and tunneling resistance. The impacts of different parameters on the interphase thickness, percolation threshold, the fraction of networked CNT, and the conductivity of nanocomposites are studied and many experimental results are used to confirm the predictions. Thin and large CNT as well as high " K " cause low percolation threshold, large conductive networks and desirable conductivity in nanocomposites. Moreover, high tunneling resistivity and large tunneling distance negatively affect the conductivity, but the exceptional CNT conductivity is ineffective. The reasonable roles of all parameters in the predicted conductivity and the fine agreement between predictions and experimental results confirm the developed model.